MENGEMBANGKAN PENELITIAN SEJARAH PEMIKIRAN EKONOMI ISLAM - MAFTUKHATUSOLIKHAH, MAFTUKHATUSOLIKHAH (Islamic Economics and Business Faculty of UIN Antasari, 2013)
As one of the social sciences, economics needs to go back to history in order to realize theexperiments and derive the change in its economic trends. This paper aims to respond to the phenomenon of the lack of serious attention has been paid to heritage of the history of Islamic economic thought by centres of academic research in economics. Exploration of the methodological framework that can be used in the study of history of Islamic economic thought, expected to attract students and researchers beginners, to do research in history of Islamic economic thought. Because of studying the history of Islamic economic thought, indeed will help us to find resources of thinking forcontemporary Islamic economic.